Feeding ofÂ dried sweet orange (Citrus sinensis) peel onÂ humoral immune response ofÂ broiler chickens - Z. Pourhossein; A. Qotbi; A. Seidavi; V. Laudadio; D. Mazzei; V. Tufarelli (International Journal of Recycling of Organic Waste in Agriculture)
Purpose An experiment was conducted to evaluate the effect of dried sweet orange (Citrus sinensis) peel (DCSP) on humoral immune response of broiler chickens. Methods Four hundred 1-day-old Ross 308 broilers were distributed according to a completely randomized design into five treatments with four replicates of 20 chicks each. The following five dietary treatments were applied: control group with 0% DCSP; diet containing 1.5% DCSP from 1 to 21 days of age (starter phase) and from 1 to 42 days of age, respectively; and diet containing 3% DCSP from 1 to 21 days of age (starter phase) and from 1 to 42 days of age, respectively. Results The DCSP treatments influenced positively total anti-SRBC and IgG titers on days 28 and 42, whereas no differences were found for IgM titer. The anti-NDV titers were not affected by diets; conversely, the anti-AIV titers were different among treatments. The anti-IBD titers were different on days 14 and 42 among diets, whereas anti-IBV titers were not influenced by treatments. Average white blood cell, heterophil, lymphocyte, and monocyte counts, as well as heterophil/lymphocyte (H/L) ratio, were different among treatments. Conclusion The findings suggested that the dietary inclusion of dried Citrus sinensis promoted some effects on the immune humoral response of chickens; however, these effects were not completely effective to protect birds from the main diseases.